2020
DOI: 10.1021/acsaelm.0c00004
|View full text |Cite
|
Sign up to set email alerts
|

Ca8Mg7Si9N22:Ce3+—A Yellow-Emitting Nitride Phosphor for White Light Emitting Diodes

Abstract: Nitridomagnesosilicate phosphors are promising candidates for white light emitting diodes. Here, we report a yellow nitride phosphor Ca 8 Mg 7 Si 9 N 22 :Ce 3+ , which exhibits a broad band emission in the spectral range of 475−675 nm under the excitation of 445 nm. The photoluminescence intensity of Ca 8−x Mg 7 Si 9 N 22 :xCe 3+ (0.01 ≤ x ≤ 0.11) reaches a maximum when x = 0.05. CIE coordinates and the color purity of Ca 7.95 Mg 7 Si 9 N 22 :0.05Ce 3+ are (0.449, 0.531) and 84.0%, respectively. The Ca 7.95 Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…5,8 Over the past two decades, many efforts have been made to develop broadband yellow phosphors, such as (La,Ca)Si 6 N 11 :Ce 3+ (FWHM: 130-143 nm, 3960-4247 cm −1 ), Ca 8 Mg 7 Si 9 N 22 :Ce 3+ (FWHM: ∼132 nm, ∼4127cm −1 ), La 3 BaSi 5 N 9 O 2 :Ce 3+ (FWHM: 167 nm, 4700 cm −1 ), Ca-α-SiAlON:Eu 2+ (FWHM: 95 nm, 2700 cm −1 ), and BaAl 2 O 4 :Eu 2+ (FWHM: ∼130 nm, 3767 cm −1 ). 4,6,[9][10][11] Similar to Ce 3+ and Eu 2+ , luminescent materials activated by Yb 2+ also exhibit broadband and tuneable emissions due to the 5d-4f transition. [12][13][14] Xie et al first reported Yb 2+ -doped oxynitride phosphors (M-α-SiAlON:Yb 2+ , M = Ca, Mg, Li, and Y), which exhibit bright green emission (λ em = 549 nm).…”
Section: Introductionmentioning
confidence: 99%
“…5,8 Over the past two decades, many efforts have been made to develop broadband yellow phosphors, such as (La,Ca)Si 6 N 11 :Ce 3+ (FWHM: 130-143 nm, 3960-4247 cm −1 ), Ca 8 Mg 7 Si 9 N 22 :Ce 3+ (FWHM: ∼132 nm, ∼4127cm −1 ), La 3 BaSi 5 N 9 O 2 :Ce 3+ (FWHM: 167 nm, 4700 cm −1 ), Ca-α-SiAlON:Eu 2+ (FWHM: 95 nm, 2700 cm −1 ), and BaAl 2 O 4 :Eu 2+ (FWHM: ∼130 nm, 3767 cm −1 ). 4,6,[9][10][11] Similar to Ce 3+ and Eu 2+ , luminescent materials activated by Yb 2+ also exhibit broadband and tuneable emissions due to the 5d-4f transition. [12][13][14] Xie et al first reported Yb 2+ -doped oxynitride phosphors (M-α-SiAlON:Yb 2+ , M = Ca, Mg, Li, and Y), which exhibit bright green emission (λ em = 549 nm).…”
Section: Introductionmentioning
confidence: 99%
“…3e), which are much better than that of other reported phosphors. 33–36 The results indicate that the LMAO:0.28Mn 2+ phosphor exhibits an excellent resistance to temperature-dependent color drifting. The luminescence lifetimes of the phosphors usually shorten when temperature-dependent quenching occurs due to an additional nonradiative contribution to the decay process.…”
Section: Resultsmentioning
confidence: 92%
“…Compared to traditional incandescent lamps, phosphor-converted white LEDs (pc-WLEDs) are extensively studied due to their long working time, environmental friendliness, and energy saving nature. In the current development of WLEDs, there are two types that have attracted much attention. In short, they are composed of the yellow phosphor plus a blue chip (WLED1) and a mixture of multiple colors plus an ultraviolet chip (WLED2). ,, With the advancement of research, yellow phosphor plays an important role in WLEDs. It should be pointed out that yellow phosphors that have both ultraviolet and blue excitation ranges are relatively rare. , The main advantage of this phosphor is that it can not only combine with blue LED chips to form another WLED1 but also mix other color phosphors with UV chips to form WLED2. In addition, unlike the narrow-band emission of rare earth ions, the broadband emission of this yellow phosphor is more suitable for current mainstream pc-WLEDs.…”
Section: Introductionmentioning
confidence: 99%